Heart Rate as a Correlate for the Emotional Processing of Body Stimuli in Anorexia Nervosa - Horndasch, Stefanie; Sharon, Elisabeth; Eichler, Anna; Graap, Holmer; Moll, Gunther; Kratz, Oliver (Behavioral Sciences, 2023)
In anorexia nervosa, aberrant emotional reactions toward body stimuli have been discussed. We investigated heart rate as a physiological marker when viewing body stimuli and hypothesized altered HR reactions toward those highly significant and emotional stimuli in anorexia nervosa. In total, 37 anorexia nervosa patients and 43 control participants viewed pictures of women of five different weight categories, while their cardiac activity was recorded. R-R intervals following picture onset were determined, and means were calculated for three distinct time periods. The overall change in HR relative to baseline across all picture categories was greater in the patient group than in the control group (significant effect of “group”, p = 0.002, partial η2 = 0.120). A significant decrease in HR 2 to 8 s after picture presentation was found for pictures of women of extreme weight in both participant groups (significant “category ∗ time segment interaction”, p = 0.01, partial η2 = 0.037) and correlated with scores of sociocultural attitudes toward the appearance for the extremely underweight category (r = −0.33, p = 0.005). Therefore, differential HR reactions for anorexia nervosa patients and control participants were found for body stimuli in general. The highest HR decelerations in response to pictures of strongly underweight and overweight women may reflect emotional processes such as anxiety due to social comparison.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adolescents; anorexia nervosa; body stimuli; heart rate